ANALISIS DEKONSTRUKSI MASKULINITAS DERRIDA DALAM IKLAN BB CREAM PRIA KOREA - Widarti Widarti; Dina Andriana; Ketut Martana (JIKE: Jurnal Ilmu Komunikasi Efek, 2020)
Abstract Related to masculinity is inseparable from discussions about gender where gender is differentfrom gender. Gender is considered as a biological construction carried out by eachindividual from birth, while gender is based on social and cultural construction. Stereotypesabout gender are masculine men and feminine women. In the adverts of BB Cream productsfrom Korea, BB Cream is not only used by women but can also be used by men. In theDANDYGUY advertisement they further promote BB Cream products for men's facialtreatments. This product imaged men also need to preen in their daily life by using BBCream. This study uses qualitative methods that can provide details about phenomena thatare difficult to explain by quantitative methods. By analyzing semiotics using Derrida'stheory of deconstruction. This research has an exploratory character, which emphasizes theprocess of the product.Keywords: Derrida, Masculinity, Gender, Semiotics.